De novo Mutations in the Cone-rod Homeobox Gene Associated with Leber Congenital Amaurosis in Chinese Patients. (March 2015) - Zou, Xuan; Yao, Fengxia; Liang, Xiaofang; Xu, Fei; Li, Hui; Sui, Ruifang; Dong, Fangtian
Abstract Background: The cone-rod homeobox (CRX) gene plays an important role in photoreceptor development. Recently, mutant alleles of the CRX gene have been associated with autosomal dominant Leber congenital amaurosis (LCA) and cone-rod dystrophy. The purpose of this study was to analyze the CRX mutations in a cohort of Chinese patients with LCA or early-onset severe retinal dystrophy (EOSRD) and to provide the clinical features of these patients. Methods: Patients with LCA or EOSRD were enrolled from 2003 to 2012. Detailed ocular examinations including optical coherence tomography (OCT) and standardized electrophysiology were performed. Genomic DNA was isolated with standard methods of genetic diagnosis. All three exons of CRX were amplified with PCR and screened for mutations through direct DNA sequencing. A total of 200 unrelated healthy Chinese subjects were screened to exclude nonpathogenic polymorphisms. Offspring-parent relationship was tested to confirm de novo mutation. Results: A total of 109 probands from 109 unrelated families were selected for mutation screening of the CRX gene. Two individuals with LCA were confirmed to carry de novo CRX mutations c.421delT (p.Ser141Pro fsX46) and c.571delT (p.Tyr191Met fsX3), respectively. The daughter of Case 1 also carried the same CRX mutation (c.421delT) and had LCA symptoms. Pigmentary retinopathy in the peripheral retina and macular atrophy were observed in the two probands. Macular atrophy without normal lamination structure was the retina phenotype under OCT. Conclusions: Two de novo mutations in CRX were found in Chinese patients with LCA. The CRX mutation might create a dominantly inherited trait.